2014
DOI: 10.4314/sajas.v43i3.7
|View full text |Cite
|
Sign up to set email alerts
|

Direct methane and nitrous oxide emissions of South African dairy and beef cattle

Abstract: The objective of this study was to estimate direct methane and nitrous oxide emissions of South African dairy and beef cattle in total and per province using the Tier 2 methodology of the Intergovernmental Panel on Climate Change (IPCC), but adapted for tropical production systems. Dairy and beef cattle in 2010 contributed an estimated 964 Giga gram (Gg) or 72.6% of the total livestock methane emissions in South Africa. Beef cattle in extensive systems were the largest contributor (83.3%), followed by dairy ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 45 publications
(40 citation statements)
references
References 17 publications
0
36
0
Order By: Relevance
“…The emission intensity of beef from specialized beef herds is almost fourfold that produced from dairy herds (68 vs 18 kg CO 2 -eq/kg of CW) because in specialized beef herds, the main production is meat, and all emissions are allocated to meat, while in dairy herds milk is the primary output and meat the secondary output, thus emissions are shared between the two outputs . The extensive beef management system uses large quantities of forage that increase gas emissions (Du Toit et al, 2013). In addition, the reproduction efficiency of cows in developing countries is low owing to nutrition and management problems, and this affects the emissions negatively.…”
Section: Beef Cattlementioning
confidence: 99%
See 1 more Smart Citation
“…The emission intensity of beef from specialized beef herds is almost fourfold that produced from dairy herds (68 vs 18 kg CO 2 -eq/kg of CW) because in specialized beef herds, the main production is meat, and all emissions are allocated to meat, while in dairy herds milk is the primary output and meat the secondary output, thus emissions are shared between the two outputs . The extensive beef management system uses large quantities of forage that increase gas emissions (Du Toit et al, 2013). In addition, the reproduction efficiency of cows in developing countries is low owing to nutrition and management problems, and this affects the emissions negatively.…”
Section: Beef Cattlementioning
confidence: 99%
“…Extensive dairy production systems (i.e. pasture) have the highest emissions, while intensively managed dairy production systems have the lowest (Du Toit et al, 2013;Scholtz et al, 2013c;Knapp et al, 2014). In South Africa, Meissner et al (2013a) found that in 2007 the emission intensity of CH 4 from dairy cows not in milk recording (average production of 4590 kg milk per cow) and in milk recording (average production of 6950 kg milk per cow) were 1.6 and 1.4 CO 2 -eq/kg of milk, respectively.…”
Section: Dairy Cattlementioning
confidence: 99%
“…Therefore the figures in Tables 1 and 2 are the result of statistics provided by the 2010 Abstract of Agricultural Statistics (DAFF, 2010a), DAFF Directorate of Agricultural Statistics Newsletter (DAFF, 2010b) and farmer support bodies (Milk SA, 2011;Mohair SA, 2011;NWGA, 2011a;RPO provincial offices, 2011;SAFA, 2011;SAGRA, 2011;SAPA, 2011;SA Pork, 2011), which were cross-checked with other references, auction sales and slaughter data (Du Toit et al, 2013a;b;c;. The game numbers are from privately owned properties (farms and reserves) and do not include those in government protected areas.…”
Section: Numbers and Distribution Of Livestockmentioning
confidence: 99%
“…In 2010, the South African Department of Agriculture, Forestry and Fisheries (DAFF) estimated the country's enteric fermentation emissions for 2004 with a Tier 2 approach for dairy and non-dairy cattle [22]. There has been further work post-2005 that estimated emissions from enteric fermentation using country-specific activity data [23,24].…”
Section: Introductionmentioning
confidence: 99%